Radiography in Diagnosis of Chronic Maxillary Sinusitis and the Common Pathogens Isolated - Tallat Najeeb , Tallat Najeeb (Journal of Rawalpindi Medical College, 2007)
Background: To determine the role of conventional radiography (R.G) in diagnosis of chronic maxillary sinusitis (CMS) and the common pathogens involved. Method: This cross sectional analytical study was conducted at Holy Family Hospital Rawalpindi over a period of two years. 25 out-door patients with signs and symptoms of CMS were included. X-Ray views of sinuses were obtained. Bilateral antral lavage (A.L) was done and the 50 sinuses evaluated. Mucopurulent irrigations were considered positive and sent for culture sensitivity. Results of antral lavage were compared with radiography. The patients were divided into four groups: True positive (T.P), False positive (F.P), True negative (T.N) and False negative (F.N). CMS was diagnosed if clinical features matched the positive A.L irrespective of R.G. Specificity of radiography (T.P and T.N results) was differentiated from its sensitivity. Most prevalent pathogens and their association with RG was determined. Results: Forty (80%) out of 50 sinuses were positive on radiography (sensitivity of R.G). Thirty-four (68%) gave positive and 16 (32%) gave clear washouts. T.P results were 25 (50%), T.N results were 02 (4%), F.P were 14 (28%) and F.N were 9 (18%). 21 out of 25 patients showed positive antral lavage leading to confirmation of diagnosis in 21 (84%) cases. Specificity of radiography was 54%. Most prevalent pathogens found were anaerobes. The sinuses infected with anaerobes were either clear or showed mucosal thickening on R.G. Conclusion: Diagnosis of CMS should not be based on conventional radiography alone. It may only be used as an adjunctive tool by correlating it with the patients’ symptoms and signs and evaluation by antral lavage